2003
DOI: 10.1176/appi.ps.54.8.1161
|View full text |Cite
|
Sign up to set email alerts
|

Use of Self-Help Services and Consumer Satisfaction With Professional Mental Health Services

Abstract: This study tested the hypothesis that users of mental health self-help services would be more satisfied with professional mental health services than clients who did not use self-help services. A survey was administered to 311 clients of professional mental health services, 151 (49 percent) of whom were users of self-help services. A multiple regression model showed that the use of self-help services was associated with greater satisfaction with professional mental health services. This finding provides suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 7 publications
2
22
0
2
Order By: Relevance
“…Previous research has shown that mutual aid groups can complement, rather than compete with, professional mental health and addiction treatment (46,47). The current study reinforces this conclusion and, despite its limitations, helps demonstrate the benefits of introducing 12-step, dual-focus mutual aid into psychiatric treatment programs that serve patients with COD.…”
Section: Discussionsupporting
confidence: 81%
“…Previous research has shown that mutual aid groups can complement, rather than compete with, professional mental health and addiction treatment (46,47). The current study reinforces this conclusion and, despite its limitations, helps demonstrate the benefits of introducing 12-step, dual-focus mutual aid into psychiatric treatment programs that serve patients with COD.…”
Section: Discussionsupporting
confidence: 81%
“…The authors hypothesize that the consumer program's organizational structure may have been no less hierarchical than that of the traditional agency, posing challenges to the promotion of better patient-centered outcomes. In a related study, Hodges et al 122 explored the relationship between the use of self-help services and professional mental health services among people who used only professional services and those who used both. Participants who used both services reported more satisfaction with professional services than the group that used only professional services.…”
Section: A Green Et Almentioning
confidence: 99%
“…Très accessibles, les OCSM rejoignent des personnes n'utilisant pas les services du réseau public ou n'y ayant pas accès (Goering et al, 2006 ;Segal, Hardiman et Hodges, 2002a). L'utilisation des services du réseau public serait plus judicieuse et plus satisfaisante (Hodges, Markward, Keele et Evans, 2003 ;Segal, Hardiman et Hodges, 2002b), et les hospitalisations moins fréquentes chez les personnes priorisant les OCSM (Burti et al, 2005). Des symptômes psychiatriques et psychologiques diminués et une qualité de vie améliorée sont d'autres facteurs positifs associés à l'utilisation des services des OSCM (Davidson et al, 1999).…”
Section: Découvrir La Revueunclassified